DGSAT: Dwarf Galaxy Survey with Amateur Telescopes: II. A catalogue of isolated nearby edge-on disk galaxies and the discovery of new low surface brightness systems - Henkel, Christian; Martínez-Delgado, David (Astronomy and astrophysics, 2017)
The connection between the bulge mass or bulge luminosity in disk galaxies and the number, spatial and phase space distribution of associated dwarf galaxies is a discriminator between cosmological simulations related to galaxy formation in cold dark matter and generalised gravity models. Here, a nearby sample of isolated Milky Way-class edge-on galaxies is introduced, to facilitate observational campaigns to detect the associated families of dwarf galaxies at low surface brightness. Three galaxy pairs with at least one of the targets being edge-on are also introduced. Approximately 60% of the catalogued isolated galaxies contain bulges of different size, while the remaining objects appear to be bulgeless. Deep images of NGC 3669 (small bulge, with NGC 3625 at the edge of the image) and NGC 7814 (prominent bulge), obtained with a 0.4 m aperture, are also presented, resulting in the discovery of two new dwarf galaxy candidates, NGC 3669-DGSAT-3 and NGC 7814-DGSAT-7. Eleven additional low surface brightness galaxies are identified, previously notified with low quality measurement flags in the Sloan Digital Sky Survey (SDSS). Integrated magnitudes, surface brightnesses, effective radii, Sersic indices, axis ratios, and projected distances to their putative major hosts are displayed. At least one of the galaxies, NGC 3625-DGSAT-4, belongs with a surface brightness of μr ≈ 26 mag arcsec-2 and effective radius >1.5 kpc to the class of ultra-diffuse galaxies (UDGs). NGC 3669-DGSAT-3, the galaxy with the lowest surface brightness in our sample, may also be an UDG.
Gesehen am 19.10.2017